Daytime napping benefits passing performance and scanning activity in elite soccer players - Nishida, M.; Okano, S.; Ichinose, A.; Suyama, S.; Youn, S. (Journal of Sports Science & Medicine, 2023)
The present study explored the effect of a daytime napping opportunity on scanning activity, which is an essential component of successful soccer performance. Fourteen male elite collegiate soccer players performed the Trail Making Test (TMT), which was used to assess complex visual attention. In addition, a soccer passing test, modified with reference to the Loughborough Soccer Passing Test, was used to evaluate passing performance as well as scanning activity. A cross-over design was applied to examine nap and no-nap interventions. Participants (N = 14, mean age: 21.6 SD = 0.5 years, height: 1.73 ± 0.06 m, body mass: 67.1 ± 4.5 kg) were randomly allocated to a midday nap (40 minutes) or no-nap group. Subjective sleepiness was measured using the Karolinska Sleepiness Scale, and perceptive fatigue was evaluated by the visual analog scale. There were no significant differences in subjective measurements or TMT between the nap and no-nap groups. However, the performance time for the passing test and scanning activity was significantly shorter (p < 0.001) and scanning activity was significantly more frequent in the nap condition than in the no-nap condition (p < 0.00005). These results suggest that daytime napping is beneficial for soccer-related cognitive function, represented by visuospatial processing and decision-making, and particularly as a potential countermeasure to mental fatigue. Considering that inadequate sleep and residual fatigue are commonly observed in elite soccer, this finding may have practical implications for the preparation of players.